2013
DOI: 10.1111/crj.12028
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos and the lung in the 21st century: an update

Abstract: The asbestos-related disorders (ARDs) are currently of significant occupational and public health concern. Asbestos usage has been banned in most developed countries, but asbestos is still used in many developing countries and the number of cases of ARDs worldwide is rising. Many countries are now experiencing an epidemic of ARDs that is the legacy of occupational exposure in the 1960s-1980s because of the long latency period between asbestos exposure and manifestation of disease. It is likely that asbestos-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(47 citation statements)
references
References 66 publications
0
45
0
2
Order By: Relevance
“…In particular interstitial lung fibrosis other than asbestosis have a very uncertain relationship with occupational exposure to asbestos. On the other hand, a number of studies demonstrated no significant association between PPs and lung function impairment, although there is still debate on this issue [19]. Data in the literature very often are conflicting and to date there are few certainties in the specific field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular interstitial lung fibrosis other than asbestosis have a very uncertain relationship with occupational exposure to asbestos. On the other hand, a number of studies demonstrated no significant association between PPs and lung function impairment, although there is still debate on this issue [19]. Data in the literature very often are conflicting and to date there are few certainties in the specific field.…”
Section: Discussionmentioning
confidence: 99%
“…In various articles in literature an association between PPs and a slight degree of lung function impairment without clinical relevance was observed. However, most studies have demonstrated no significant association between PPs and abnormal pulmonary function tests [19]. Spanish guidelines for the diagnosis and management of asbestos-related pleural and pulmonary disease consider that PPs in general do not cause a decrease in pulmonary function and when it appears, it would be due to other concomitant causes, such as the onset of interstitial fibrosis or smoking [20].…”
Section: Pleural Plaques Lung Function and Risk Of Malignant Asbestomentioning
confidence: 99%
“…They demonstrated that the level and localization of pleural irregularities significantly differed between patients with benign asbestos pleural effusion and PM. In this sense fluorodeoxyglucose PET/CT has been shown to be a useful diagnostic tool for differentiate PM from benign PPs [7]. Probably these difficulties have affected research in the specific field.…”
Section: Discussionmentioning
confidence: 99%
“…The awareness of potential asbestos hazards needs to be increased because of the long latency period between asbestos exposure and manifestation of ARDs [23]. Many efforts had been paid on the updated evidence-based methodology of an appropriate health surveillance program for asbestos-exposed population [24].…”
Section: Discussionmentioning
confidence: 99%